2019
DOI: 10.5812/msnj.90409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distraction Therapy on Physiological Indices and Pain Intensity Caused by Intra-Spinal Injection of Chemotherapy Drugs in Cancerous Children: A Clinical Trial

Abstract: Background: One of the non-pharmacological methods for relieving pain in children is to deploy cognitive-behavioral interventions such as distraction therapy. Objectives: The aim of the present study was to examine the impact of distraction on physiological indices and the severity of pain caused by intra-spinal injection of chemotherapy drugs in children with cancer. Methods: This was a clinical trial with a pretest-posttest design. The subjects included 89 cancerous children aged 6-12 years who had been admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
2
0
2
Order By: Relevance
“…This finding is consistent with Wong et al (2020) (20) , who stated that leukemia is considered the most common type of cancer in childhood, Similarly, the study findings align with Yang & Cho (2019) (21) , who reported that nearly two-thirds of pediatric cancer patients suffer from hematologic malignancies. Additionally, the findings agree with Fooladi et al (2019) (22) , who found that more than two-thirds of pediatric patients were affected by acute lymphoblastic leukemia (ALL). Regarding the clinical manifestations experienced by the studied children receiving chemotherapy, the current study highlights that more than half of them suffered from weight loss, and less than one-quarter experienced insomnia.…”
Section: High Anxiety Moderate Anxiety Low Anxietysupporting
confidence: 91%
“…This finding is consistent with Wong et al (2020) (20) , who stated that leukemia is considered the most common type of cancer in childhood, Similarly, the study findings align with Yang & Cho (2019) (21) , who reported that nearly two-thirds of pediatric cancer patients suffer from hematologic malignancies. Additionally, the findings agree with Fooladi et al (2019) (22) , who found that more than two-thirds of pediatric patients were affected by acute lymphoblastic leukemia (ALL). Regarding the clinical manifestations experienced by the studied children receiving chemotherapy, the current study highlights that more than half of them suffered from weight loss, and less than one-quarter experienced insomnia.…”
Section: High Anxiety Moderate Anxiety Low Anxietysupporting
confidence: 91%
“…Lo anterior, se asemeja a los resultados de otros estudios recientes basados en intervenciones cognitivo conductuales, dentro de las cuales se emplearon ya sea la relajación o la distracción, y que buscaban entre otras cosas, la reducción del malestar subyacente de los tratamientos de quimioterapia con pacientes oncológicos (Orozco et al, 2016;Fazelniya et al, 2017;Larios et al, 2018;Fooladi et al, 2019;Mikaeili et al, 2019;Zhang et al, 2019;Chirico et al, 2020). Sin embargo, el aspecto diferencial de la presente investigación apuntó a la combinación de las dos técnicas señaladas, con un objetivo en pág.…”
Section: Discussionunclassified
“…Larios et al (2018), reportan en sus resultados, que las técnicas de relajación aplicadas a pacientes bajo tratamiento de quimioterapia, lograron reducir síntomas de tensión, ansiedad y estrés percibidos. Investigaciones similares realizadas con niños con cáncer encontraron que la intervención basada en la distracción sirvió para disminuir el malestar emocional y el dolor causados por los procedimientos de quimioterapia (Fooladi et al, 2019;Mikaeili et al, 2019). A través de una intervención que incluía la reestructuración cognitiva y la relajación, dirigida a pacientes chinos que llevaban tratamiento de quimioterapia, Zhang et al (2019) concluyeron que estas técnicas favorecen la reducción del malestar.…”
Section: Pág 8875unclassified
“…The study supported with Saged, Yusoff & Abdul Latif (2020) (58) who concluded that the Holy Quran sound is an effective treatment for spiritual and psychological issue that reduce anxiety and pain intensity. Also, Fooladi, et al, (2019) (61) concluded that distraction therapy can be effective in minimizing the severity of pain caused by intra-spinal injection of chemotherapy drugs in cancerous children and improving hemodynamic indices. Concerning anxiety level in the current study, there was lowering in the anxiety level posttest compared to pre-test in the Qur'an group compared to the Music group and there was a highly statistically significant difference between two groups post-test.…”
Section: Discussionmentioning
confidence: 99%